2010
DOI: 10.1111/j.1863-2378.2010.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Dirofilariosis in South‐East Serbia‐Case Report

Abstract: Human dirofilariosis is a relatively rare infection caused by filarial worms of the genus Dirofilaria. We herein report the first case of human subcutaneous dirofilariosis in the southeastern part of Serbia. A complete alive nematode was removed from a nodule in the periorbital region of a 50-year-old woman. The nematode was morphologically identified as a D. repens-like immature female. The diagnosis was confirmed with molecular methods. The patient was probably infected in the South-East Serbia as she had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…According to Džamić et al (2009), until 2008 a total of 28 cases had been reported of which 19 occurred in the period from 2001 to 2008. The southernmost reports on human dirofilariosis are from Vranje and Prizren where the patients had worms in the subconjunctival and periocular tissues (Tasić et al, 2011;Jakšić et al, 2011). A recent study has shown that seroreactivity to D. repens antigens was found in 29 out of 297 people examined (9.8%) from 7 different areas of Serbia (Tasić-Otašević et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Džamić et al (2009), until 2008 a total of 28 cases had been reported of which 19 occurred in the period from 2001 to 2008. The southernmost reports on human dirofilariosis are from Vranje and Prizren where the patients had worms in the subconjunctival and periocular tissues (Tasić et al, 2011;Jakšić et al, 2011). A recent study has shown that seroreactivity to D. repens antigens was found in 29 out of 297 people examined (9.8%) from 7 different areas of Serbia (Tasić-Otašević et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some researchers suggest that wild carnivores such as foxes may be significant wild reservoirs for zoonotic filarioids (Magi et al, 2008). With an exception of a few studies on the presence of microfilariae in the blood of domestic dogs (Tasić et al, 2008(Tasić et al, , 2012Kočevski et al, 2010) and human dirofilariosis case reports (Stefkov and Gjorgov, 1967;Cvetković et al, 2007;Džamić et al, 2009;Tasić et al, 2011;Jurhar Pavlova et al, 2012), no research has been conducted so far on wild animals, either in Serbia or in the Former Yugoslav Republic of Macedonia. The aim of this study was to present the first data on D. repens in wild canids from the Central Balkan and to help understand the importance of these species as hosts and potential reservoirs of dirofilariosis in nature.…”
mentioning
confidence: 99%
“…By this epidemiological evidence in dogs, many cases of human infection should be expected, but instead, only about 30 cases have been reported to date [3,14]. This apparent disagreement urged us to investigate the actual frequency of infectious contacts between the two filarial parasites and human population, and to analyze possible risk factors for the infection, which would be useful in planning the appropriate control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first case of the human ocular, subconjunctival dirofilariosis on the territory of the southeast Serbia and the city of Niš. Note that in this case there was no history of patient's trips or stay in other parts of Serbia, such as Vojvodina which is considered as a hyperendemic area for D. repens in dogs (16,(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%